Thonningia sanguinea Vahl. (Balanophoraceae) in Southern Nigeria: II. Patterns of Genetic Diversity and Population Structure within and between Populations - Imarhiagbe, Odoligie; Aigbokhan, Emmanuel Izaka (Makara Journal of Science, 2019)
Studies have yet to assess the genetic variability in Thonningia sanguinea populations in Southern Nigeria. Hence, this study was conducted to elucidate the pattern of genetic variability and population structure among T. sanguinea populations in Southern Nigeria. Genomic DNA was extracted from 31 individuals in 15 populations and tested using random amplified polymorphic DNA (RAPD) primers. Several genetic diversity parameters were examined using GenALEx Ver. 6.5. Reproducible RAPD markers indicated that all the sampled populations were composed of individuals with a high genetic variability. The populations were grouped into four distinct clusters. The populations from the Okour community forest had high gene diversity and Shannon index. Conversely, the populations from Cross River National Park had the lowest gene diversity and Shannon index. Genetic variability did not correlate with geographic distances. Analysis of molecular variance revealed that most (82.3%) of the diversities could be explained by allelic variations within the population. An indirect estimate of gene flow yielded gave an Nm of 1.09, indicating a low migration level among populations. Results demonstrated that T. sanguinea populations in Southern Nigeria exhibited outcrossing strategy expected of the sexual exchange of gametes by different individuals within a local population.